3D Electron Diffraction Structure Determination of Terrylene, a Promising Candidate for Intermolecular Singlet Fission. Issue 15 (30th June 2021) - Hall, Charlie L.; Andrusenko, Iryna; Potticary, Jason; Gao, Siyu; Liu, Xingyu; Schmidt, Werner; Marom, Noa; Mugnaioli, Enrico; Gemmi, Mauro; Hall, Simon R.
Abstract: Herein we demonstrate the prowess of the 3D electron diffraction approach by unveiling the structure of terrylene, the third member in the series of peri ‐condensed naphthalene analogues, which has eluded structure determination for 65 years. The structure was determined by direct methods using electron diffraction data and corroborated by dispersion‐inclusive density functional theory optimizations. Terrylene crystalizes in the monoclinic space group P 21 / a, arranging in a sandwich‐herringbone packing motif, similar to analogous compounds. Having solved the crystal structure, we use many‐body perturbation theory to evaluate the excited‐state properties of terrylene in the solid‐state. We find that terrylene is a promising candidate for intermolecular singlet fission, comparable to tetracene and rubrene. Abstract : Terylene for singlet fission ? 3D electron diffraction (ED) is used to overcome a gap in the crystallographic knowledge, by reporting the first structural solution of terylene. Cutting‐edge computational analysis show that terylene has the potential to act as an effective singlet fission chromophore. This represents a substantial milestone in evolution of 3D ED, by demonstrating that hitherto unobtainable structures can be used in the prediction of physical properties of functional materials.